تأثير إضافة زيتي الميرمية ودوار الشمس في بعض صفات الجودة والخصائص الوظيفية للنقانق المصنعة محلياً بالاستبدال الجزئي الدهن الحيواني : الاوميغا ٣ في خلطات النقانق (Journal of Hama University, 2022)
The aim of the research is to evaluate the quality indicators and the functional characteristics of prepared sausage mixes, according to which a stable emulsion is obtained using sheep fat, Before and after the heat treatment، This research was conducted in the laboratories of the Department of Biotechnology and Food Sciences at the Faculty of Agricultural Engineering - University of Damascus, during the period between August and November of 2019. emulsions from Beef were prepared by partial replacement of sheep fat with vegetable oils (chia + sunflower). The prepared emulsions differed among themselves in the amount of vegetable oils used in the mixture and the percentage of added animal fat; Where the percentage of chia seed oil ranged between (1-5%) and the proportion of sunflower oil between (4-20%) and the percentage of added fat between (5-30%), while the control was free from both chia seed and sunflower oils. The indicators of the studied quality were represented by chemical properties (Moisture, Protein, Fat and TBA), physical properties (emulsion stability, PH and WHC) and microbial properties (coliform and pseudomonas). As for the functional properties, tests were included to determine the proportion of polyunsaturated fatty acids in the studied mixtures. The results showed that the mixture(T4) which containing sheep fat (10%), chia seed oil (4%) and sunflower oil (16%) was superior, as it was found that the high proportion of polyunsaturated fatty acids was higher during the storage period (C18: 1 = 33.2 ± 0.2 - C18: 2 = 35.1 ± 0.1) after storage for ten days, while the value of C18: 3 = 8.2 ± 0.3) was the highest at the beginning of storage, as it was found that the value of thiobarbituric acid (TBA) decreased after ten days storage (0.357 ± 0.02), and high The emulsion stability value (50 ± 2) after storage for five days, In addition to the decrease in the microbial content after storage for ten days for both coliform (0) and pseudomonas (0.1 ± 0.75) compared with the rest of the mixtures during the storage period, The mixture T4 surpassed the control after subjecting it to heat treatment (boiling then frying), in which the amount of protein increased (22.8%) , the value of cooking yield (95%) , it was free of both coliform bacteria and pseudomonas, its sensory properties were good and increase of the amount of unsaturated fatty acids in it, especially C18 : 2 (34.74%).